PROCEDURE FOR REPAIRING PUBLIC TRANSPORT BUSES - Rakhimjonov , Muslimjon Ravshanjon o‘g‘li; Khikmatov, Ravshan Saidumarovich (Educational Research in Universal Sciences, 2023)
The increase in demand for public transport means that it needs to be continuously operated. This article points out the importance of keeping public transport buses in working condition and provides ideas on maintenance.